A abordagem do ensino de estatística nos livros de matemática do ensino médio - Perugini, Everton [UNIFESP] (2020)
This paper aimed to investigate and debate the math textbooks approach in regards to the teaching of statistics in high school. It is expected that such dissertation could be useful to improve the quality of high school mathematics’ teaching as well as of graduation courses in mathematics. Considering the high school teachers, this paper plays the role of provoking reflections and assisting in the planning and practice of statistics classes. For teachers of graduation courses in mathematics, the objective was to present a portrait of the teaching methodology for statistics reflected in the high school literature and, thus, approximate statistics academic knowledge to the high school classes’ practice. The proposed focus of this paper is relevant as there are discrepancies among the different high school textbooks’ approaches related to statistics; besides, the accelerated process of changes in the official mathematics curriculum in recent years incentives the verification of whether or not the textbooks are in line with government guidelines. As for the methodology applied, it was basically a research in the format of analysis of textbooks, with emphasis on the presence, depth and correctness of statistical content. The research was supported mainly by government publications such as the “Base Nacional Comum Curricular Base (BNCC)”, for example, to justify the presence or the absence of statistical topics in high school. In addition, three high school math textbooks were analyzed: “Matemática Contexto e Aplicações”, “Matemática Paiva” , “Contato matemática”. These publications were indicated by the “PNLD - Programa Nacional dos Livros Didáticos”; the purpose here is to verify the approach utilized for teaching statistics and to compare the official guidelines versus the analyzed textbooks. After analyzing the data, notes were made on the need to adapt or not the topics covered in high school literature. It was confirmed that the analyzed textbooks must be adapted to meet the demands of government regulation, allowing individuals to have a more active participation on the learning process with exercises that not only allow simple interpretation but also provides the student a more active, creative and critical approach on such process.